Efektivitas Deep Learning terhadap Kemampuan Bernalar Kritis Siswa - Sastrawati, Desvina; Haifaturrahmah, Haifaturrahmah; Nizaar, Muhammad (Mataram University, 2025)
This study aims to review the effectiveness of deep learning in enhancing students’ critical reasoning skills through a Systematic Literature Review (SLR) approach. Data were collected from Google Scholar, DOAJ, and Scopus databases covering publications from 2015 to 2025, using the keywords “deep learning,” “critical reasoning,” and “higher-order thinking.” A total of 20 selected articles were analyzed based on relevance, research design, and findings. The results indicate that deep learning effectively enhances students’ abilities to analyze, evaluate, and reflect by engaging them in meaningful and contextual learning processes. The most effective models include Problem-Based Learning (PBL), Project-Based Learning (PJBL), and Case-Based Learning, which foster collaboration and higher-order thinking. The success of deep learning implementation is also determined by the teacher’s role as a facilitator who cultivates a reflective and critical classroom culture. Therefore, integrating deep learning into instructional design is recommended as an innovative strategy to strengthen students’ critical reasoning and prepare them for 21st-century education challenges.